2018
DOI: 10.1038/s41419-018-0699-2
|View full text |Cite
|
Sign up to set email alerts
|

Profiling and functional analysis of circular RNAs in acute promyelocytic leukemia and their dynamic regulation during all-trans retinoic acid treatment

Abstract: Circular RNAs (circRNAs) are a novel class of powerful regulators in gene expression and participate in the pathogenesis of many diseases, including cancer. However, little is known about the roles of circRNAs in the development and treatment of acute promyelocytic leukemia (APL). Here we report the expression profiling and function of circRNAs in APL, including their dynamic regulation during all-trans retinoic acid (ATRA)-induced differentiation. We performed two independent ribosomal RNA-minus RNA-sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 59 publications
1
38
0
Order By: Relevance
“…The overall cir-cRNA expression profiles at these three time points were uniform and not significantly altered by MERS-CoV infection. Collectively, these basic characteristics of the putative circRNAs identified in our study were similar to those identified in other human and mammalian cells, including mouse P19 embryonic carcinoma, human neuroblastoma SH-SY5Y, and acute promyelocytic leukemia-derived NB4 [38][39][40].…”
Section: Landscape Of Circrnas Mirnas and Mrnas Identified In Humansupporting
confidence: 77%
“…The overall cir-cRNA expression profiles at these three time points were uniform and not significantly altered by MERS-CoV infection. Collectively, these basic characteristics of the putative circRNAs identified in our study were similar to those identified in other human and mammalian cells, including mouse P19 embryonic carcinoma, human neuroblastoma SH-SY5Y, and acute promyelocytic leukemia-derived NB4 [38][39][40].…”
Section: Landscape Of Circrnas Mirnas and Mrnas Identified In Humansupporting
confidence: 77%
“…Influence ATRA-induced differentiation of APL cells [155] circ-DLEU2 ↓in pediatric AML-M5 Hypermethylation of DLEU2 affected prognosis [156] ↑in CN-AML patients BMand AML cell lines…”
Section: -3pmentioning
confidence: 99%
“…In recent years, the research of circRNAs, as one of ncRNAs, is focused on their function as "miRNA sponges" in the complex endogenous RNA networks. A circRNA HIPK2, for example, sponged miR-124-3p to regulate the differentiation of all-trans retinoic acid (ATRA)-induced NB4 cells [155]. Chen et al [151] reported that circANAPC7 was significantly upregulated in AML and used an Arraystar human circRNAs microarray and bioinformatics analysis to predict when ANAPC7 might bind miR-181 family to participate in AML pathogenesis.…”
Section: Prognostic Value Of Lncrnas In Acute Myeloid Leukemiamentioning
confidence: 99%
“…Recently, three-lncRNA expression-based risk score was developed based on RNA-seq data for AML patients using two leading data repositories [Therapeutically Available Research to Generate Effective Treatments (TARGET) and The Cancer Genome Atlas (TCGA)]. According to prognosis modelling, which was developed based on survival data, the combination of the lncRNA risk score and cytogenetics risk group provided a higher prognostic value than any of the individual prognostic factor [61].…”
Section: Clinical Significance Of Ncrnas In Leukemiamentioning
confidence: 99%